Magnetic anisotropy phase-graded A1/L10-FePt films on amorphous glass substrates. (5th June 2017) - Barucca, G.; Speliotis, Th.; Giannopoulos, G.; Niarchos, D.; Rutkowski, B.; Czyrska-Filemonowicz, A.; Agostinelli, E.; Laureti, S.; Testa, A.M.; Varvaro, G.
Abstract: Magnetic anisotropy phase-graded A1/L10 -FePt films deposited on amorphous glass substrates were investigated combining ultra-high resolution electron microscopy and angular-dependent magnetic measurements. A highly textured (001) L10 FePt film was first deposited at the relative low temperature of 625 K using an MgO/Cr underlayer stack, hence a second layer was grown while continuously decreasing the deposition temperature down to a final value ranging from 515 K to 365 K depending on the layer thickness ( t g ). This procedure leaded to the formation of a phase-graded system consisting of hard and soft magnetic phases separated by a rough nanometer-size interphase boundary, where the magnetic anisotropy gradually changes due to the variation of the relative amount of hard and soft phases across the whole film thickness. Electron microscopy analysis allowed the structure of the samples to be investigated at an atomic level. The A1 and L10 -FePt phases were localized inside the film and the orientation relationships between their lattices were determined. The samples show a preferential perpendicular anisotropy up to t g = 15 nm and a significant reduction of the coercive field with the increase of the graded layer thickness ( 30% for t g = 5 nm), suggesting their potential application as magnetic recording media. Graphical abstract: Highlights: Perpendicular FePt-based phase-graded films were deposited on glass substrates. Microstructural properties were investigated at atomic level. A rough nanometer-size L10 /A1 interface forms. Coercivity significantly decreases with the increase of the graded layer thickness.